2012
DOI: 10.1007/s11262-012-0715-z
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the S gene region of hepatitis B virus genotype D in Golestan Province-Iran

Abstract: Mutations of HBsAg especially within the "a" determinant could alter the antigenicity of the protein causing failure of HBsAg neutralization and escaping from the host's immune system, resulting in active viral replication and liver disease. This project aimed to investigate mutation in the S gene region of HBV infected patients in Golestan Province-Iran. HBV-DNA extractions from plasma and PCR of 100 patients were performed. Direct sequencing and alignment of S gene were applied using reference sequence from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 23 publications
4
15
1
Order By: Relevance
“…2000; Yong- Lin et al, 2012;Simon et al, 2013;Yao et al, 2013;Pezzano et al, 2011;Baclig et al, 2014;Lee et al, 2005;Moradi et al, 2012;Lin et al, 2013;Salpini et al, 2015). In contrast, two substitutions N131A observed here in a patient whose serum sample tested HBsAg-negative at time of HBV-R (pt 10) and S136F (pt 5) were not, to our knowledge, previously described.…”
Section: Amino Acid Variability Within Hbsagcontrasting
confidence: 62%
“…2000; Yong- Lin et al, 2012;Simon et al, 2013;Yao et al, 2013;Pezzano et al, 2011;Baclig et al, 2014;Lee et al, 2005;Moradi et al, 2012;Lin et al, 2013;Salpini et al, 2015). In contrast, two substitutions N131A observed here in a patient whose serum sample tested HBsAg-negative at time of HBV-R (pt 10) and S136F (pt 5) were not, to our knowledge, previously described.…”
Section: Amino Acid Variability Within Hbsagcontrasting
confidence: 62%
“…This finding was in agreement with the results of other studies, especially in genotype D-infected patients [22,56]. In our study group, nearly half of the mutations (44.3%) occurred in the CTL epitope, suggesting a narrowly focused immune selection pressure at a hot spot position.…”
Section: Discussionsupporting
confidence: 94%
“…Of course, part of it may be related to the small sample size. In another study in Iran, P120T/S and R122K/T were found in 4% of patients, and G145R was found only in one case (13); which none of them occurred in the current project. These mutations frequently occurred and it was suggested that this frequency may be due to the pressure of the immune system or vaccine on their selection, considering the fact that these patients did not receive NAs.…”
Section: Discussionmentioning
confidence: 41%
“…The HBsAg ‘‘a’’ determinant (amino acids 124 - 147) is located within the major hydrophilic region (MHR, amino acids 99 - 169) of this surface protein (12) which produces the potent B-cell epitope of HBs Ag(13), and it has been proven that amino acid substitutions within this region produce escape mutants. Immune escape mutants allow for the replication of HBV in vaccinated persons (14, 15), since antibodies induced by current vaccines do not recognize critical changes in the surface antigen domain (16).…”
Section: Introductionmentioning
confidence: 99%